Optimalisasi Pemberdayaan Kader dan Digitalisasi Pos Pelayanan Terpadu Lansia dan Balita Kota Tanjungpinang Berbasis Mobile dan Web - Safitri, Liza; Huda, Dwi Nurul; Romdoni, Mochammad Rizki; Winarni, Ade; Haris, Muhammad; Bizli, Fikramul (Universitas Nusantara PGRI Kediri, 2025)
Posyandu Sei Jang Laut and Aisyiyah in Tanjungpinang still rely on a manual recording system that is prone to errors and less efficient. Duplication of data that occurs between notebooks, Excel reports, and PDFs is an obstacle in managing toddler growth data. To overcome these problems, the community service team developed a mobile and web-based toddler and elderly information system. This application is designed to integrate all posyandu participant data, both toddlers and elderly, as well as monitor the growth of toddlers more efficiently and accurately, and produce output in the form of participant reports and toddler development so that it can be immediately analyzed and used for decision making. The results of the evaluation of the application show that it is easy to access the application 61.5% agree and 38.5% strongly agree. The application can support posyandu administration 69.2% strongly agree. And overall satisfaction with the application 62.9% strongly agree and 30.8% agree. With the existence of mobile and web-based toddler and elderly information systems can improve the quality of posyandu services by providing accurate data so that empowering posyandu cadres in carrying out their duties is assisted by the use of information technology so as to improve the quality of public health in Tanjungpinang.